Work Of Legal Products Traffic In Overcoming Road Conclusion - Fadli Fadli; Akhmad Khisni (Law Development Journal, 2021)
The purpose of this study is to examine and analyze the concept of the substance of traffic law products in overcoming road congestion. This research uses a normative juridical method with research specifications in the form of descriptive analysis. Based on the discussion, it is concluded that the state's efforts in the form of legislation with the existence of legal products that are correlated with overcoming the problem of congestion on the highway with various concepts of interrelated substances include Act No. 22 of 2009, concerning traffic and transportation. Act No. 23 of 2014 concerning Regional Government in Article 9 paragraph (1) states that there are 3 (three) types of government affairs, namely absolute government affairs, concurrent government affairs, and general government affairs. Government affairs under the authority of the Regions consist of Mandatory Government Affairs and Preferred Government Affairs. Article 10 of Act No. 38 of 2004 concerning Roads states that to regulate road use and smooth traffic, roads are divided into several road classes. Government Regulation Number 32 of 2011 concerning Management and Engineering, Impact Analysis, and Traffic Needs Management, the scope of regulation of PP Management and Engineering, Impact Analysis, and Traffic Needs Management includes traffic management and engineering activities including planning, regulation, engineering, empowerment, and supervision.